Thrombus imaging with fibrin-specific gadolinium-based MR contrast agent EP-2104R: results of a phase II clinical study of feasibility - Vymazal, Josef; Spuentrup, Elmar; Cardenas-Molina, Gerardo; Wiethoff, Andrea J; Hartmann, Michael G; Caravan, Peter; Parsons, Edward C (Investigative radiology, 2009)
PURPOSE: To determine the feasibility of detecting thrombi using a fibrin-specific gadolinium-based magnetic resonance imaging contrast agent, EP-2104R. METHODS: Subjects with confirmed thrombus in the venous system (n = 14), or in the heart, or arterial system (n = 38) were enrolled. Patients were imaged before and at various times following a 4 mumol/kg intravenous bolus injection of EP-2104R: <1 hour (N = 16), 2 to 6 hours (N = 36), and/or 20 to 36 hours (N = 33). Images were assessed by investigators at each site and by a single reader not affiliated with the sites to determine whether thrombi were visible, not visible, or further enhanced with EP-2104R. A subset of data was analyzed quantitatively by measuring a signal intensity relative to background tissue. RESULTS: Overall, 29 thrombi were visible before contrast administration, 3 of 14 in the venous system, and 26 of 38 in the arteries and heart. Thrombi generally enhanced in signal after EP-2104R injection, and an additional 7 were visualized. After contrast, 4 of 14 thrombi were visible in the venous system, and 32 of 38 in the arteries and heart. Thrombi were more conspicuous when imaged at 2 to 6 hours post EP-2104R compared with within 1 hour, because of lower blood background. Quantitatively, the post: pre signal intensity ratio was 1.90 at 2 to 6 hours post injection (standard deviation = 1.08, N = 20, P < 0.001); and 2.04 (standard deviation = 1.29, N = 19, P < 0.0025) for the 20 to 36 hours time point. There were no serious adverse events considered related to study drug. CONCLUSION: EP-2104R enhanced magnetic resonance imaging detects thrombi not readily visible in precontrast screening and gives additional enhancement of thrombi that are visible in precontrast imaging.
Keywords: dospělí; Magnetic Resonance Imaging; Female; Feasibility Studies; Adult; mladý dospělý; ženské pohlaví; Reproducibility of Results; Fibrin; lidé; trombóza; Sensitivity and Specificity; magnetická rezonanční tomografie; vylepšení obrazu; Aged, 80 and over; senzitivita a specificita; Image Enhancement; Middle Aged; peptidy; reprodukovatelnost výsledků; studie proveditelnosti; Male; Aged; kontrastní látky; Young Adult; Drug Delivery Systems; gadolinium; fibrin; Thrombosis; lidé středního věku; senioři nad 80 let; lékové transportní systémy; senioři; mužské pohlaví; Contrast Media; Peptides; Gadolinium; Humans